Is Blood Pressure Improving in Children With Chronic Kidney Disease?: A Period Analysis. Issue 3 (March 2018) - Barletta, Gina-Marie; Pierce, Christopher; Mitsnefes, Mark; Samuels, Joshua; Warady, Bradley A.; Furth, Susan; Flynn, Joseph
Abstract : Uncontrolled hypertension in children with chronic kidney disease (CKD) has been identified as one of the main factors contributing to progression of CKD and increased risk for cardiovascular disease. Recent efforts to achieve better blood pressure (BP) control have been recommended. The primary objective of this analysis was to compare BP control over 2 time periods among participants enrolled in the CKiD study (Chronic Kidney Disease in Children). Casual BP and 24-hour ambulatory BP monitor data were compared among 851 participants during 2 time periods: January 1, 2005, through July 1, 2008 (period 1, n=345), and July 1, 2010, through December 31, 2013 (period 2, n=506). Multivariable logistic regression to model the propensity of a visit record being in period 2 as a function of specific predictors was performed. After controlling for confounding variables (age, sex, race, socioeconomics, CKD duration, glomerular filtration rate, proteinuria, body mass index, growth failure, and antihypertensives), no significant differences were detected between time periods with respect to casual BP status (prehypertension: 15% versus 15%; uncontrolled hypertension: 18% versus 17%; P =0.87). Analysis of ambulatory BP monitor data demonstrated higher ambulatory BP indices, most notably masked hypertension in period 2 (36% versus 49%; P <0.001). Average sleep BP index ( P <0.05) and sleep BP loads ( P <0.05) were higher in period 2. Despite publication of hypertension recommendations and guidelines for BP control in patients with CKD, this study suggests that hypertension remains undertreated and under-recognized in children with CKD. This analysis also underscores the importance of routine ambulatory BP monitor assessment in children with CKD. Abstract : Supplemental Digital Content is available in the text.